HUBUNGAN KESADARAN KOMUNIKASI SBAR PERAWAT DENGAN PENINGKATAN KUALITAS PELAYANAN KEPERAWATAN DI RSU BUNDA THAMRIN MEDAN - Sontina Saragih; Hutagaol, Aureliya; Purba, Dahlia (Jurnal Ilmiah Keperawatan IMELDA, 2023)
Nurses play an important role in improving the quality of health services, especially nursing. Quality of nursing services as a continuous and patient-centered care process. Nurse communication is a vital factor in determining high-quality nursing services. This study aims to analyze the relationship between awareness of nurses' SBAR communication and improving the quality of nursing services at Bunda Thamrin Medan General Hospital. This research is descriptive correlational by using a cross-sectional approach. The population of this study was all nurses in the inpatient room of Bunda Thamrin Medan General Hospital, totaling 225 nurses with a sampling technique, namely total sampling according to the inclusion criteria. Data were analyzed through the chi-square test (x2). The results of the study found that there was a significant relationship between SBAR communication awareness and the quality of nursing services at Bunda Thamrin General Hospital Medan (p-value 0.013). The conclusion is that nurses' SBAR communication supports quality nursing services. So, it is hoped that the hospital's management will provide SBAR communication assistance for new nurses and evaluate the implementation of SBAR communication periodically and provide rewards for compliance with the implementation of SBAR communication.